Curl: a language for web content. (28th August 2007) - Ward, Steve; Hostetter, Mat
We describe a language designed for the representation of a broad spectrum of web content, including formatted text, graphics, and programmed application-level function. The approach described maps conventional markup tags to underlying, more general programming constructs, and provides local extensibility of the markup language by addition of programmed objects, procedures, and macros to the underlying object-oriented programming language. An implementation strategy based on a mix of static and dynamic just-in-time compilation techniques is described. The discussion focuses on a number of specific technical challenges raised by the language's breadth and performance goals, and the impact of these issues on Curl's architecture.